Quantification of Friction Force on Dual-Axis Micro-Mechanical Probe for Friction Force Microscopy - Hiroaki Amakawa (Japanese Society of Tribologists, 2010)
Conventional friction force microscopes (FFMs), where micro cantilever probes are used, have a disadvantage that the accurate quantification of friction force has not been established yet. This comes from the difficulty of measurement of the probe torsion angle. On the other hand, a recently developed dual-axis micro-mechanical probe does not require the torsion angle but the lateral displacement for the quantification of friction force. This probe measures the friction force with a double cantilever beam and the normal force with a torsion beam. Since the measurement of the lateral displacement is easier than that of the torsion angle, the dual-axis micro-mechanical probe is expected to provide more accurate and reproducible quantification. In this paper, we investigated two calibration methods for dual-axis micro-mechanical probes; probe adhesion and step structure methods. The probe adhesion method showed rather poor reproducibility for the lateral displacement detection. In contrast, the step structure method showed good reproducibility and good accuracy with the minimum detection limit of the order of 0.1 nm, which corresponds to the friction force of sub-nN for the probes with a spring constant of the order of 1 N/m. The dual-axis micro-mechanical probe can be used to quantify the nanotribological properties accurately.